The energy cost of ski mountaineering: effects of speed and ankle loading - Tosi, P.; Leonardi, A.; Schena, F. (The Journal of Sports Medicine and Physical Fitness, 2009)
Aim. The purpose of this study is to determine the energy cost (EC) of ski mountaineering and its variation with speed and ankle loading. Methods. Seven male skiers volunteered to participate in this study. Field tests (500 m, gradient 21%) were executed on packed snow at an altitude of about 1 600 m. Measurements were carried out breath by breath by a portable gas analyzer. Energy cost of uphill skiing was calculated from the steady state VO2. In the speed protocol each subject was asked to repeat the same route at three different speed levels. In the weight protocol, subjects were instructed to maintain the preferred speed for three trials on the same track while wearing different weight bands on their ankle. Results. At the self-selected speed of 1.07±0.05 m s-1 and without extra load beside the normal equipment, the mean value of EC on packed snow is 10.6±0.4 J kg-1m-1. A percentage variation of the speed (%speed) produces a corresponding percentage variation of the energy cost %EC = 0.32 · %speed. The %EC as a function of the percentage of added load, %weight, with respect to the total weight of the subject, including ski, bindings, and boots is given by %EC = 1.71 · %weight. Conclusion. Data obtained in the present study constitute the first quantitative description of EC for ski mountaineering and result higher than for walking or snowshoeing. Effects due to ankle loading appear negligible for recreational skiers, while they should be taken into account in agonistic competition.